Scores of Brunei Lower Secondary School Students on Emotional Intelligence Variables: Exploring the Differences - Masri, Norfaezah (Glob J Health Sci, 2016)
The survey compared the emotional intelligence of 254 (128 females) randomly selected Year 11 Brunei Cambridge General Certificate of Education (BCGCE) Ordinary Level students using the six subscales of the BarOn Emotional intelligence scale – youth version. Females scored significantly higher on the intrapersonal variable than males. However, males sored much higher on the positive impression subscale. In addition, students aged 16 scored significantly higher on the interpersonal scale than all others. However, the 15-year olds scored highest on the adaptability and positive impression scales than their peers. Furthermore, participants who reported that they were not so much satisfied with their personal life scored significantly higher on the interpersonal scale than their counterparts. Moreover, participants who consult friends when faced with problems scored significantly higher on the interpersonal variable while those who search the internet for solutions to problems scored higher than others on the adaptability scale. No significant differences were obtained on any subscale when participants were compared on the basis of their parents’ marital status as well as the type of guardian they stayed / lived with. Implications of the findings are discussed and mixed-methods research was recommended.